2011
DOI: 10.1007/s00792-011-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3

Abstract: Trehalose is a chemical chaperone known to protect a variety of organisms against cold stress. Members of the genus Arthrobacter, which belongs to the Actinomycetales group, exhibit strong resistance to stress conditions, but exactly how trehalose synthesis is regulated in conditions of cold stress is still unknown. Here, we report that Arthrobacter strain A3, which was isolated from the alpine permafrost, has only two trehalose synthesis pathways (OtsA/B and TreS), while other Arthrobacter spp. have three. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In E. coli , trehalose synthesis by enzymes OtsA and OtsB is induced by cold shock and is essential for cell viability [ 44 ]. In the psychrotolerant bacterium Arthrobacter strain A3, trehalose serves as a source of carbon, allowing cells to maintain normal metabolism at prolonged low temperatures [ 45 ]. Additional pathways for trehalose biosynthesis from maltose by the enzyme trehalose synthase ( treS ), and from maltodextrin by malto-oligosyl trehalose synthase ( treY ) and malto-oligosyl trehalose trehalohydrolase ( treZ ), were also identified in all Antarctic and temperate Arthrobacter genomes.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli , trehalose synthesis by enzymes OtsA and OtsB is induced by cold shock and is essential for cell viability [ 44 ]. In the psychrotolerant bacterium Arthrobacter strain A3, trehalose serves as a source of carbon, allowing cells to maintain normal metabolism at prolonged low temperatures [ 45 ]. Additional pathways for trehalose biosynthesis from maltose by the enzyme trehalose synthase ( treS ), and from maltodextrin by malto-oligosyl trehalose synthase ( treY ) and malto-oligosyl trehalose trehalohydrolase ( treZ ), were also identified in all Antarctic and temperate Arthrobacter genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the psychotrophic Arthrobacter strain A3, the Ar51 has the stronger ability to synthesis trehalose as the osmotic stress protector (Chen et al, 2011;Sun et al, 2016). In the genome of Ar51, it contains three pathways to synthesis trehalose: the OtsA/B (AU252_RS06465, AU252_RS06470, AU252_RS12615), TreY/TreZ (AU252_RS17210, AU252_RS17205) and TreS (AU252_RS10705, AU252_RS06525) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…An otsA deletion mutant (Ar0002) has significantly reduced intracellular trehalose levels compared to the wild-type strain, Ar0001 ( S1A Fig ) [ 24 ]. We also observed that the mutant exhibits an apparent markedly slower growth rate in low osmolarity medium as determined by optical density (OD 600 ; Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Arthrobacter sp. strain A3 (hereafter referred to as Arthrobacter A3), a psychrotrophic bacterium, was isolated from the alpine permafrost of the Tianshan Mountains in China [ 24 ]. It has an optimal growth temperature of 20 0 C, but can survive and grow at near-freezing temperatures as low as -4 0 C. Its stress tolerance is in part due to synthesis of trehalose catalyzed by OtsA/B [ 25 ] .…”
Section: Introductionmentioning
confidence: 99%